Pengadaan Barang Dan Jasa Menurut Perpres No.54 Tahun 2010 Pada BPK RI Perwakilan Provinsi Jawa Timur Sebagai Bagian dari Good Governance - Bambang Jatmiko (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2013)
The procurement of goods and services is the one of important factors for supporting the establishment of government’s rod and development, which is written in the Rule of President Number 54 Year 2010. The procurement of government’s goods and services cannot been separated from the struggle of the government to achieve their vision and mission. This struggle is implemented by doing this action according to the Rule of President Number 54 Year 2010. The procurement of government’s good and services are easily influenced by corruption, colution, and nepotism that commonly found in birocracy. Those actions will give bad effects to the government’s finance, because only few people consumes the money, but the others do not. Consummating of rules, training of understanding for the whole commitee of the procurement of government’s goods and services, and fixing the process of government’s good and services procurement which can be applied to reduce the leak of budget may be an important aspect to reform government’s finance in these years. One of the strategies to reduce corruption, collusion, and nepotism, the government shall choose the staff according to President Rules Number 54 Year 2010, in order to make this condition better. Which are the strategies: 1. The recruitment of the staffs still influenced by the structural position, so the procurement of government’s goods and services can be held without any corruption, transparently, and independently. 2. Mechanism of Direct Procurement as a new method of mechanism according to President Rule Number 54 Year 2010, which is the reform of President Decrit Number 80 Year 2003, is still needed to understand and implement. According to those problems, the writer will have some research to find out the conformity of the real procurement of goods and services in BPK-RI East Java province and the President Rule Number 54 Year 2010. The writer hopes this procedure may be held transparently, accountability, and well manage.Keyword: pengadaan barang dan jasa, perpres 54 Tahun 2010, good governance